2007
DOI: 10.1007/s11103-006-9106-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the cytoplasmic male sterility-associated orf456 gene of chili pepper (Capsicum annuum L.)

Abstract: Cytoplasmic male sterility (CMS) in plants is known to be associated with novel open reading frames (ORFs) that result from recombination events in the mitochondrial genome. In this study Southern and Northern blot analyses using several mitochondrial DNA probes were conducted to detect the presence of differing band patterns between male fertile and CMS lines of chili pepper (Capsicum annuum L.). In the CMS pepper, a novel ORF, termed orf456, was found at the 3'-end of the coxll gene. Western blot analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 51 publications
10
125
0
2
Order By: Relevance
“…2c-4, c-5). These phenotypes of aberrant floral organs in transgenic B. rapa are similar with others studies (Yang et al 2010 andKim et al 2007). …”
Section: Phenotypes Of Orf456 Transformantssupporting
confidence: 91%
See 3 more Smart Citations
“…2c-4, c-5). These phenotypes of aberrant floral organs in transgenic B. rapa are similar with others studies (Yang et al 2010 andKim et al 2007). …”
Section: Phenotypes Of Orf456 Transformantssupporting
confidence: 91%
“…In the previous study, a CMS-associated gene, orf456 was found at the 3' -end of the coxII gene, which was identified as a strong candidate for determining the malesterile phenotype in pepper (Kim et al 2007). When this gene was ectopically expressed in Arabidopsis, transgenic plants showed abnormal pollen development and sterility.…”
Section: Chimeric Gene Construction and Transformationmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel and chimeric mitochondrial sequences are a frequent result of this recombination (Wise et al, 1987;Kennell and Pring, 1989;Wen and Chase, 1999;Gallagher et al, 2002;Okazaki et al, 2013;Yamagishi and Bhat, 2014;Tang et al, 2017), in which recombination sometimes leads to the creation of transcripts that interfere with normal male gametophyte development (Kitazaki and Kubo, 2010) via the generation of toxic and/or disruptive transmembrane proteins (Korth et al, 1991;Kim et al, 2007;Wan et al, 2007;Zhang et al, 2007;Yang et al, 2009;Gulyas et al, 2010;Jing et al, 2012;Flores-Renteria et al, 2013;Ji et al, 2013;Luo et al, 2013;Okazaki et al, 2013;Park et al, 2013;Hu et al, 2014). Surprisingly, such genes are not only abundant in many fertile plants, such as Arabidopsis thaliana Unseld et al, 1997), Beta vulgaris (Kubo et al, 2000), Oryza sativa (Notsu et al, 2002), Brassica napus (Handa, 2003), Zea mays (Clifton et al, 2004), Triticum aestivum (Ogihara et al, 2005), and Nicotiana tabacum (Sugiyama et al, 2005), but are also constitutively expressed.…”
Section: Discussionmentioning
confidence: 99%